2016
DOI: 10.1038/srep22113
|View full text |Cite
|
Sign up to set email alerts
|

The fusion protein SS18-SSX1 employs core Wnt pathway transcription factors to induce a partial Wnt signature in synovial sarcoma

Abstract: Expression of the SS18/SYT-SSX fusion protein is believed to underlie the pathogenesis of synovial sarcoma (SS). Recent evidence suggests that deregulation of the Wnt pathway may play an important role in SS but the mechanisms whereby SS18-SSX might affect Wnt signaling remain to be elucidated. Here, we show that SS18/SSX tightly regulates the elevated expression of the key Wnt target AXIN2 in primary SS. SS18-SSX is shown to interact with TCF/LEF, TLE and HDAC but not β-catenin in vivo and to induce Wnt targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 54 publications
1
46
0
Order By: Relevance
“…Similar to prior studies [22,25], we observed frequent b-catenin expression in synovial sarcoma. Synovial sarcoma is characterized by translocation t(X; 18)(p11; q11) [26], resulting in SS18 gene rearrangement with one of three SSX gene fusion partners (SSX1, SSX2, or SSX4); SS18-SSX activation of the Wnt signaling pathway has been demonstrated using in vitro and in vivo studies [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to prior studies [22,25], we observed frequent b-catenin expression in synovial sarcoma. Synovial sarcoma is characterized by translocation t(X; 18)(p11; q11) [26], resulting in SS18 gene rearrangement with one of three SSX gene fusion partners (SSX1, SSX2, or SSX4); SS18-SSX activation of the Wnt signaling pathway has been demonstrated using in vitro and in vivo studies [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…SS18-SSX while serving as a bridge between activating transcription factor 2 (ATF2) and transducin-like enhancer of split 1 (TLE1), resulted in repression of ATF2 target genes. Besides, the fusion oncoprotein SS18-SSX via TCF/LEF, TLE1 and HDAC interaction leads to an upregulation of AXIN2, which is involved in the WNT pathway but without direction interaction with the pathway 33 . Romidepsin significantly suppressed the growth of synovial sarcoma cells compared with that of osteosarcoma, as it impacted SS18-SSX target gene expression by preventing TLE1 complex recruitment 34, 35 .…”
Section: Molecular Mechanisms Of Hdis In Sarcomamentioning
confidence: 99%
“…The fusion of SSX to SS18 also recruits interacting proteins involved in epigenetic regulation, including transducin-like enhancer of split 1 (TLE1), activating transcription factor 2 (ATF2), members of the polycomb group and histone deacetylases (HDAC) [5, 6]. Together, this is thought to bring about the abnormal transcriptional pattern that drives malignant transformation in synovial sarcoma [4, 5].…”
Section: Introductionmentioning
confidence: 99%